Analisis Yuridis Wanprestasi Perjanjian Waralaba Menurut Peraturan Pemerintah Nomor 42 Tahun 2007 Tentang Waralaba (Studi Kasus Perjanjian Waralaba PT X Dengan Mitra Di Surabaya) - Dinadi, Naura Aisyla; Wahyudi, Eko (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze legal protection for franchisee in implementing the franchise agreement. A franchise is an agreement between two parties where the parties are the giver and recipient of the franchise. A franchisor is "a person or business entity that gives franchisees the right to use the franchise they own". Meanwhile, a franchisee is "an individual or business entity who is given the right by the franchisor to utilize and/or use the franchise owned by the franchisor". The type of research used is normative juridical which is descriptive in nature with a statutory approach (the statute approach) and uses types of data from library materials which are usually called secondary data. The results of the analysis in this paper show that, in practice, franchise agreements based on the case study of this decision have not been implemented correctly in accordance with Government Regulation no. 42 of 2007 concerning Franchising and there are still many defaults that occur in franchise agreements. Settlement of default cases in enforcing legal protection for franchisees is carried out through efforts to resolve them through the adjudication process and consensus process. In carrying out this franchise agreement, franchisees and franchisors should carry out their obligations in accordance with the mutually agreed agreement so that cases of default can be minimized so that both parties benefit.